Pengaruh Kinerja Keuangan Terhadap Return Saham Dengan Menjadikan Kebijakan Dividen Sebagai Variabel Moderate Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Indeks ( JII 2007 – 2011) - Angga Kurniawan (Akuisisi: Jurnal Akuntansi, 2017)
The company's financial performance is one of the factors seen by investors as a consideration to invest funds in a company by making the financial statements as a source of information. Good and bad corporate performance can show how much profit can be earned each year and will have an impact on management in setting dividend policy for investors. This study was conducted to determine the effect of financial performance on stock returns by making dividend policy as a moderate variable. Objects taken in this study amounted to 7 companies listed on the Jakarta Islamic Index (JII) for 5 consecutive years from 2007-2011. Dependent variable of this research is stock return, independent variable include Current Ratio, Return on Asset, Return on Equity, Debt to Equity Ratio, and Total Turnover Asset, while dividend policy (Dividend Payout Ratio) as moderate variable. The method used in this study is Multiple Linear Regression Method and Moderate Regression Analysis Method (Moderate Regrestion Analysis).Based on the results of multiple linear regression analysis seen from the value of significance shows that CR, ROA, ROE, and DER does not significantly influence the stock return, whereas TATO shows the result that there is a significant influence on stock return. The result of moderate regression analysis shows that the dividend policy is not able to moderate the effect of financial performance on stock return. Keywords: Financial performance (CR, ROA, ROE, DER, TATO), stock return, dividend policy (DPR).